DTU's blade research and demonstration platform. Issue 1 (October 2020) - Haselbach, Philipp U; Semenov, Sergei; Berring, Peter
Abstract: At DTU Wind Energy, a 12.6 m wind turbine rotor blade and the corresponding blade moulds were designed and manufactured to establish a blade research and demonstration platform. The blade research and demonstration platform shall allow manufacturing of a blade or blade segments under controlled conditions, allowing realizing theoretical concepts and testing these in full-scale for materials, manufacturing and design concepts of next generation wind turbines. For this purpose, the entire blade design with detailed airfoil and structural design as well as the manufacturing and test data of the blade will be published. Static tests, fatigue tests, post-fatigue static tests as well as a modal testing of the manufactured rotor blade are planned to characterize the blade response. In this way, the DTU 12.6m wind turbine rotor blade and the blade moulds can serve as a reference rotor blade to benchmark numerical simulations and to test new materials, designs, manufacturing concepts or embedded sensors for future prognostics health management systems. In this article, results of a 3D scan of the blade moulds are presented as well as description of the water-based heating and cooling system and a resistance temperature detectors (RTD) measuring system.